FUNGSI MUSIK KALASON OTO SEBAGAI HIBURAN DALAM BUDAYA TRANSPORTASI MASYARAKAT SUMATRA BARAT - Winaldo, Hafiz; Darlenis, Teti (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2024)
In this research, the author uses the concept of music function from Alan P. Meriam. After understanding the problem of the function of music contained in oto kalason (literally: car horn), from this concept, it can be explained that oto kalason functioned as the only entertainment in West Sumatran society at that time (especially when traveling by bus), both inside traveling by oto-oto (buses) at that time, or in people's daily activities. The horns on public transport buses at that time could play songs, sing, even the profession of being a car horn player was quite promising at that time. This horn sound is what many people have been waiting for, a sound that is loved by many people. This is a genre that has long colored the lives of the people of West Sumatra and the transportation (buses) of that time.